INTEGRASI KOMUNIKASI PEMASARAN DALAM KONSEP PARIWISATA BERKELANJUTAN “KAMPUNG ADAT SEGUNUNG” - Sheidy Yudhiasta; Garsione Agni Andrea; Leily Suci Rahmatin (Universitas Muhammadiyah Gresik, 2023)
This study examines the implementation of integrated marketing communication as a concept of sustainable tourism in Kampung Adat Segunung. The research methodology is qualitative. Data was collected by interviews, observations, and documentary studies. The participants in this research are divided into two groups, namely the key informants and the supporting informants. The key informants are the initiators who founded the